Establishment of a cell-based assay to screen regulators for Klotho gene promoter - XU Zhi-liang; GAO Hong; OU-YANG Ke-qing; CAI Shao-xi; HU Ying-he (Acta Pharmacologica Sinica; Vol 25, No 9 (September 2004): Acta Pharmacologica Sinica, 2016)
AIM: To discover compounds which can regulate Klotho promoter activity. Klotho is an aging suppressor gene. A defect in Klotho gene expression in the mouse results in the phenotype similar to human aging. Recombinant Klotho protein improves age-associated diseases in animal models. It has been proposed that up-regulation of Klotho gene expression may have anti-aging effects. METHODS: Klotho promoter was cloned into a vector containing luciferase gene, and the reporter gene vector was transfected into HEK293 cells to make a stable cell line (HEK293/KL). A model for cellular aging was established by treating HEK293/KL cells with H2O2. These cells were treated with extracts from Traditional Chinese Medicines (TCMs). The luciferase activity was detected to identify compounds that can regulate Klotho promoter. RESULTS: The expression of luciferase in these cells was under control of Klotho promoter and down-regulated after H2O2 treatment. The down-regulation of luciferase expression was H2O2 concentration-dependent with an IC50 at approximately 0.006 %. This result demonstrated that the Klotho gene promoter was regulated by oxidative stress. Using the cell-based reporter gene assay, we screened natural product extracts for regulation of Klotho gene promoter. Several extracts were identified that could rescue the H2O2 effects and up-regulated Klotho promoter activity. CONCLUSION: A cell -based assay for high-throughput drug screening was established to identify compounds that regulate Klotho promoter activity, and several hits were discovered from natural products. Further characterization of these active extracts could help to investigate Klotho function and aging mechanisms.